ЎЗБЕКИСТОН ИҚТИСОДИЁТИГА ТЎҒРИДАН-ТЎҒРИ ХОРИЖИЙ ИНВЕСТИЦИЯЛАРНИ ЖАЛБ ҚИЛИШДА ДАВЛАТ ИНСТИТУТЛАРИНИНГ ЎРНИ - Муртозаев, Сардорбек (Innovatsion texnologiyalar, 2022)
The article analyzes the role of foreign direct investments in the development of the country’s economy and the role of public institutions in actively attracting foreign investments. By analyzing the management indicators in the World Bank’s "Worldwide Governance Indicators" database and the data of the "Doing Business 2020" report, institutional problems, which are the main obstacles in attracting direct foreign investments to Uzbekistan, are indicated, and relevant suggestions and recommendations are given for institutional reforms that should be implemented.